ANALISIS PERBEDAAN BIAYA MEDIK LANGSUNG PASIEN DIABETES MELITUS TIPE 2 - Pande Made Desy Ratnasari; Tri Murti Andayani; Dwi Endarti (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Type 2 diabetes mellitus (T2DM) is a chronic disease that requires high costs for lifelong therapy. Direct medical costs associated with the cost of antidiabetic and complications. The aim of the study was to determine the difference in direct medical costs based on antidiabetic prescribed and complications. The study design was cross-sectional. Data was taken retrospectively based on medical records and financial data in September 2017 at Panembahan Senopati Hospital Bantul Yogyakarta. Subjects in this study were 200 patients with inclusion criteria were type 2 DM outpatient, aged â‰¥18 years and received routine antidiabetic at least 3 months before the study. Exclusion criteria are patients with pregnant or breastfeeding. Analysis of differences in direct medical costs based on antidiabetic prescribed and complications using the Kruskal Wallis while sociodemographic were reviewed descriptively. The results showed 48.5% of patients with type 2 DM received combination oral and insulin. The most common complication was macrovascular (19.5%). The average direct medical cost was Rp489.005.00. There is a difference in direct medical costs based on antidiabetic prescribed (p=0.000) and complications (p=0.000). Patients receiving combination with oral and insulin and patients with macrovascular and microvascular complications have the highest direct medical costs.